Identifying regional green infrastructure hotspots. A comparison between the Basilicata and Campania regions, Italy - Isola, Federica; Lai, Sabrina; Leccis, Francesca; Leone, Federica (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Assessing ecosystem services (ESs), the goods and benefits provided by ecosystems and necessary to maintain human life and well-being, is important in spatial planning. Indeed, land-use changes allowed, or even driven, by spatial plans can alter ecosystem structure and functions, thereby influencing ES supply, and, ultimately, the quality of the environment and of human life. Within this framework, this study proposes a methodological approach for the identification of ES hotspots, defined as key areas that supply high levels of ESs, to support more sustainable spatial planning. The initial phase comprises a biophysical evaluation of three key regulating ESs: habitat quality, representing the capacity of ecosystems to sustain wildlife; carbon storage and sequestration, reflecting their contribution to climate regulation; and land surface temperature, serving as an indicator of local thermal mitigation offered by ecosystems. In the second phase, multiple spatial statistical methods for hotspot detection are employed in an integrated framework. Applied to Campania and Basilicata in southern Italy, the proposed approach makes it possible to compare extent and distribution of ES hotspots in the two regions. Easily transferable to other contexts where biophysical ES assessments are available, this approach provides planners with useful information to support effective planning choices.